Platelet Rich Plasma for Treatment of Rheumatoid Arthritis: Case Series and Review of Literature. (3rd February 2020) - Badsha, Humeira; Harifi, Ghita; Murrell, William D.
Abstract : Platelet-rich plasma (PRP) is an autologous blood product with platelets above circulating levels and releases several growth factors after activation. PRP may help to decrease joint inflammation by modulating synovial cell proliferation and differentiation and inhibition of catabolic pathways in various articular conditions. Though PRP has shown good efficacy in osteoarthritis and other musculoskeletal conditions such as synovitis, epicondylitis, skeletal muscle injuries, and tendinopathy, there is limited experience for the use of PRP in patients with rheumatoid arthritis. Precise mechanisms of action of PRP are not known. We present clinical experience for treatment with PRP (2–4 ml) in four patients with rheumatoid arthritis who had inadequate response and persistent pain and inflammation with intra-articular steroids. Irrespective of past and ongoing treatments and duration of disease, all patients showed improvement in the visual analog scale and disease activity score of 28 joints at 4 and 8 weeks after injection. There was an improvement in joint inflammation on ultrasound imaging in some patients. These effects were sustained for up to 1 year. No adverse effects were reported in any patient. PRP may be a safe and useful therapy in patients with rheumatoid arthritis who fail to respond to one or more established treatment options.